On norms and their transgression in serious leisure: two case studies from rock climbing. Issue 3 (26th May 2016) - Wood, Martin
Abstract : As interest grows in the subject of sport, play and games as social practice, it becomes more important to elaborate on the contribution serious leisure makes in the formation of hegemonic power and the margins of everyday life. There are alternative models of what constitutes serious leisure and in particular the experience of leisure transgression. Case study based qualitative data are presented which illuminate several important influences within two settings featuring the adventure activity of rock climbing. I suggest that organisation and organising is one of a range of factors impinging on the theme of serious leisure. An implication is that climbers in the present may have more difficulty than did their predecessors in resisting both the encroachment of rationalised society and capture by market driven forces.